Research-Based Practices for Reintegrating Students With Emotional and Behavioral Disorders From the Juvenile Justice System. (April 2018) - Mathur, Sarup R.; Griller Clark, Heather; LaCroix, Leslie; Short, James
This article discusses the unique and influential role of school teachers in the rehabilitation and reintegration of students with emotional and behavioral disorders who have been involved with the juvenile justice (JJ) system. By adopting evidenced-based practices, highlighted within this article, teachers can prevent further escalation of students' negative behaviors and repeated involvement in the JJ system.